Efficiency of solar bowl model using aluminum-zinc alloy coated steel based reflector - Dan, Jun Xian (2012)
Working concept of Solar Bowl is to concentrate the solar radiation onto a receiver by a group of reflector plate. There are two specific objectives for this study, first is to design the reflector alignment using Catia software; second is to determine the energy efficiency of the model. 55% aluminum-zinc alloy metallic coated steel was used as the reflector. The previous work of other researchers and the Sun-Earth geometry will be studied. The design of heliostat of other researchers will be used as reference for the design of heliostat for solar bowl UPM. Water was used to conduct the efficiency test. The basic concept of efficiency of the model Solar Bowl UPM is output power divided by input power. Output power is the total energy to heat up the water temperature over certain time duration. Input power is the total solar power entering into the solar bowl model in the same time duration. Catia software was used to determine the suitable alignment of the reflector plate. The geometry of the reflector was designed according to the Law of Reflection. The reflection pattern of the solar ray was simulated. An efficiency test was conducted to determine the efficiency of the solar bowl model. Efficiency test for the solar bowl model was conducted for 30 days.